Statistical analysis plan for the ‘Triple Antiplatelets for Reducing Dependency after Ischaemic Stroke’ (TARDIS) trial - Bath, Philip M.W.; Robson, Katie; Woodhouse, Lisa J.; Sprigg, Nikola; Dineen, Robert A.; Pocock, Stuart J. (SAGE Publications, 2015)
Rationale: Antiplatelet agents such as aspirin, clopidogrel and dipyridamole are effective in reducing the risk of recurrence after a stroke. Importantly, the risk of recurrence is highest immediately after the index event while antiplatelets cause bleeding. Aims and/or hypothesis: The ‘Triple Antiplatelets for Reducing Dependency after Ischaemic Stroke’ (TARDIS) trial is testing whether short-term intensive antiplatelet therapy is safe and effective in reducing the early risk of recurrence as compared with standard guideline-based therapy. Design: TARDIS is an international multi-center prospective randomized open-label blinded–end-point trial, with funding from the UK Health Technology Assessment program. Patients with acute ischemic stroke or transient ischemic attack are randomized within 48 h to intensive/triple antiplatelet therapy or guideline antiplatelets taken for one-month. Patients or relatives give written informed (proxy) consent and all sites have research ethics approval. Analyses will be done by intention-to-treat. Study Outcome: The primary outcome is shift in stroke recurrent events and their severity, assessed using the modified Rankin Scale, at three-months. Discussion: This paper and attachment describe the trial’s statistical analysis plan, as developed from the protocol during recruitment and prior to unblinding of data. The statistical analysis plan contains design and methods for analyses, and unpopulated tables and figures for the primary and baseline publications. The data from the trial will provide the first large-scale randomized evidence for the use of intensive antiplatelet therapy for preventing recurrence after acute stroke and transient ischemic attack.